Izzivi mestu po informacijski revoluciji - Petrešin, Vesna (Urbani izziv, 2000)
The paper compares the predictions and guessing about the development of cities and the living culture at the beginning of the information revolution to the current trends. The information revolution being a fact nowadays, its consequences reflect in social and environmental phenomena, in changes in culture and aesthetics and remains of the past industrial era-the monuments of the future. The potential interest of neighbourhoods is related to agglomeration of central functions as a reflection of global economy that is parallel to a metamorphosis of production process, working schedule and new forms of jobs. There is a significant demand in flexible building types, temporary access to new media and the related services. With the augmented virtual capacity of a city, the e-neighbourhoods also grow. The city becoming a hybrid of the built and the digital offers new challenges to the architectural and urban planning profession.
Keywords: informacijska družba; informacijska tehnologija; informatika; information science; information technology; mesta; telecommunication; telekomunikacije; urbana sociologija; urbani razvoj; urbanism; urbanizem